Noverre’s lament: inscription, posterity, and the ephemeral art of dance - Sabee, Olivia (Status Quaestionis, 2025)
Jean-Georges Noverre defined pantomime ballet, or ballet d’action, as an ephemeral art. In his published writings, Noverre argued that to notate a ballet’s movement was both inadequate – in that the present day’s dance notation could not record a pantomime ballet – and inappropriate – in that the passions, the core of pantomime ballet, could not be recorded as discrete, repeatable units the way steps could have been. At the same time, Noverre was deeply invested in posterity, both his own, and that of pantomime ballet as a form. This essay examines the values of ephemerality and posterity in the writings of Noverre, reconciling the contradictions inherent in these values by considering Noverre’s views on what he considers appropriate means of documentation in view of future readers and dancers.